High-resolution typing of HLA-DRB1 locus in the Macedonian population - A. Petlichkovski; O. Efinska-Mladenovska; D. Trajkov; T. Arsov; A. Strezova; M. Spiroski (Wiley Online Library, 2004)
The Macedonian population is of special interest for HLA anthropological study in the light of unanswered questions regarding its origin and relationship with other populations, especially the neighbouring Balkanians. Two studies have been performed to examine HLA molecular polymorphism in the Macedonian population, so far. The present study is the first to be performed in Macedonia using high-resolution sequence-based method for direct HLA typing. The study included 158 unrelated healthy volunteers of Macedonian origin and nationality, having a Christian Orthodox religion. After the simultaneous amplification of exon-2 on both HLA-DRB1 alleles, DNA sequencing was used for genotype assignment. In the 158 samples analysed, all 316 alleles were typed and a total of 29 different DRB1 alleles were detected, with DRB1*1601 being the most frequent allele (14.9%), followed by DRB1*1104 (13.9%). A phylogenetic tree constructed on the basis of the high-resolution data deriving from other populations revealed the clustering of Macedonians together with other Balkan populations (Greeks, Croats, Turks and Romanians) and Sardinians, close to another "European" cluster consisting of the Italian, French, Danish, Polish and Spanish populations. The included African populations grouped on the opposite side of the tree.